Las relaciones CTSA con la formación de maestros en contextos de vulnerabilidad - Valencia Valbuena, Fredy Gregorio; Giraldo, Carmen (Revista Científica, 2011)
The elective courses "Teaching Working with Communities in displacement condition” attached to the Department of Physics, Faculty of Science and technology, the Universidad Pedagógica Nacional, has done the theoretical and practical, the reflexion practical pedagogical work with the communities living in the suburbs of Soacha (Altos de Cazucá), places that show the migration of the population living in displacement conditions (Codhes, 2009).This has led to the University as an institution to prepare teachers to assume the ethical and political responsibility with the big problems of education in Colombia, and for this it contributes to the development of a set of meaningful Offers of students from various curricula programs beginning with the role of the teacher in certain contexts of extreme social vulnerability, for which it is proposed to link the disciplines with the context, in view of the formation of participatory for making desizion based on the problems from their environment that contribute to the search for alternative solution from the approach of situations through dialogue, listening, arguing and being controversia (Caamaño, 1995), in this sense it is articulated vulnerable scenarios as enablers to work together (teachers-students-community) focus on contributions of the science, technology, society and environment (CTSA).